Swiss Monetary Targeting 1974-1996: The Role of Internal Policy Analysis - Georg Rich (Swiss Journal of Economics and Statistics, 2007)
After the switch to a floating exchange rate in 1973, the Swiss National Bank at first adopted annual monetary targets and in the 1990s shifted to a medium-term targeting strategy. In this paper I review the SNB's internal policy analysis, an aspect of Swiss monetary targeting that has received little attention in the existing literature. I show that money played a key role in setting monetary policy and in communicating the SNB's decisions to the public. Due to the adoption of monetary targets, the SNB was able to reduce the inflation trend to low levels. However, it was less successful in preserving price stability during business-cycle expansions because the monetary targets did not call for a sufficiently pre-emptive policy stance. At the end of 1999, the SNB abandoned monetary targeting in favour of an approach based on inflation forecasts.
Keywords: E31; E32; E41; E52; E58; 330; Monetary policy; monetary targets; policy rules; price stability